Electro Magnetic Wireline Retrievable-Surface Controlled Subsurface Safety Valve: A New Backup For Surface Controlled Subsurface Safety Valve To Avoid WorkOver - Imbò, P.; Gandini, G. (Journal of Petroleum Research and Studies, 2011)
The scope of this document is to summarize the field trial of Expro FlowCaT and Geoservices GEM-Valve Wireless Electromagnetic Surface Controlled Sub-surface Safety Valve in Fiume Treste field, in sud of Italyt and provide a final technical evaluation. In 2007, COMP started a study about existing Surface Controlled Sub-surface Safety Valve, to have a complete knowledge of their status in worldwide wells and to make a statistic analysis of the most common failures. The control line‟s failure is the most critical, since it prevents the installation of a contingency WR-SCSSV, which would be impossible to control. In these cases, the only available contingency, till now, was the installation of a SSCSV (Sub-Surface Controlled Safety Valve), but it doesn‟t guarantee the same level of reliability as the SCSSV‟s: These valves are not controlled from the surface, they are not fail-safe and they are operated by particular events on the well (such as high flow rate or low pressure), which are very uncertain. To address this issue, COMP made a survey with valves‟ suppliers and a solution to, this problem was identified in the new wireless electromagnetic technology. After a strict “ISO-modified” qualification process and a 6-months field installation in a STOGIT gas storage well with monthly tests and a final slam test, both the considered Electromagnetic Wireless Surface Controlled Sub-surface Safety Valves: Expro 3.65” FlowCaT & Geoservices 3.72” GEM-VALVE are considered qualified and field proven to be installed in eni wells.